Hemorrhagic shock secondary to spontaneous rupture of a nonsecretory adrenal cortical tumour: A case report - Jarral, Omar A.; Todd, Colin; Willson, Peter D. (Canadian Urological Association Journal, 2013)
A 21-year-old female presented with left-sided loin pain and profound circulatory shock. After emergency laparotomy, angiography, embolisation and histological investigation, a diagnosis of spontaneous rupture of a benign non-secretory adrenal cortical tumour was made. To our knowledge, this is the only reported case of this diagnosis.